Possible Inscriptional Attestation to Sergius Paul[L]US (Acts 13:6–12), and the Implications for Pauline Chronology - Campbell, Douglas A. (The journal of theological studies, 2005)
A re-examination of an inscription found in Chytri on Cyprus suggests a possibly highly significant, though challenging, piece of further evidence for the reconstruction of Paul's life. This evidence is fragile because the inscription is very partial, but certain concrete considerations previously not remarked on suggest restoring the emperor's name in line 9 as Tiberius, and that of the Roman citizen in line 10 as Quintus Sergius Paul[l]us. Quintus Sergius was also probably the island's governor. It would follow from this restoration—which must be treated with appropriate caution—that Paul's ‘first missionary journey’, as recounted in Acts 13–14, took place during or before 37 ce, the year of Tiberius’ death. This is roughly ten years earlier than is usually thought to be the case, although it is by no means impossible in absolute terms. This conclusion renders the strictly sequential—and foundational—use of information from Acts for the reconstruction of Paul's life highly problematic.